Structural and Functional Comparison of SARS-CoV-2-Spike Receptor Binding Domain Produced in Pichia pastoris and Mammalian Cells - Zelada, Alicia Mercedes (2020)
The yeast Pichia pastoris is a cost-effective and easily scalable system for recombinant protein production. In this work we compared the conformation of the receptor binding domain (RBD) from SARS-CoV-2 Spike protein expressed in P. pastoris and in the well established HEK-293T mammalian cell system. RBD obtained from both yeast and mammalian cells was properly folded, as indicated by UV-absorption, circular dichroism and tryptophan fluorescence. They also had similar stability, as indicated by temperature-induced unfolding (observed Tm were 50 °C and 52 °C for RBD produced in P. pastoris and HEK-293T cells, respectively). Moreover, the stability of both variants was similarly reduced when the ionic strength was increased, in agreement with a computational analysis predicting that a set of ionic interactions may stabilize RBD structure. Further characterization by HPLC, size-exclusion chromatography and mass spectrometry revealed a higher heterogeneity of RBD expressed in P. pastoris relative to that produced in HEK-293T cells, which disappeared after enzymatic removal of glycans. The production of RBD in P. pastoris was scaled-up in a bioreactor, with yields above 45 mg/L of 90% pure protein, thus potentially allowing large scale immunizations to produce neutralizing antibodies, as well as the large scale production of serological tests for SARS-CoV-2.